Answer:
3x+1.
Explanation:
First we divide g(x)/f(x) (the process is in the first image):
5x-15 in Z7[x] is 5x-1 and
is
in Z7[x]. So
g(x)/f(x) =
![(5x-1)(x^3+3x^2+6x+1)+3x^2+2x+2](https://img.qammunity.org/2020/formulas/mathematics/college/gs3y2z59xr4jtmombx6jfdn4pxojsamxmi.png)
Now gcd(g,f) = gcm(f,r).
f(x)/r(x) =
![5x(3x^2+2x+2) + 3x+1](https://img.qammunity.org/2020/formulas/mathematics/college/teyk322o3b1mfihqi220dykofaivk8u64y.png)
Then, gcd(f,r) = gcd(r,3x+1).
r/(3x+1) =
![(x+5)(3x+1) +4](https://img.qammunity.org/2020/formulas/mathematics/college/5vjvr5riqv419zcln8sxd9wedcxxgqydgk.png)
Then, gcd(r, 3x+1) = gcd(3x+1,4) = 3x+1.
So, gcd(f,g) = 3x+1.